Ultrasonic Analysis of the Influence of Structure on Tropical Soil Behavior - Pereira, Géssica Soares; Pitanga, Heraldo Nunes; Ferraz, Roberto Lopes; Rodrigues, Roger Augusto [UNESP]; de Paula Rodrigues, Klaus Henrique; Nalon, Gustavo Henrique (Springer Nature, 2025)
Advancing the current understanding of the effects of tropical soil structure on their mechanical behavior is challenging due to the difficulty of isolating different structural effects on soil response. Limited research has been conducted on the potential use of ultrasonic techniques to interpret structural effects on the performance of tropical soils. This study aimed to assess the influence of structure on the behavior of a residual clayey tropical soil, in terms of compressibility and collapse susceptibility. The analyses were supported by microstructural and ultrasonic evaluation. Different soil structures were created by subjecting the soil to distinct reconstitution techniques and moisture contents, while maintaining the same dry unit weight and void ratio values, but changing the particle bonding conditions (with or without cement addition). The experimental program included geotechnical and microstructural characterization, ultrasonic pulse velocity tests, and oedometer tests at different inundation stages. The results showed the influence of particle organization, void ratio, artificial cementation, and moisture content on the soil compressibility and collapse susceptibility. The addition of cement to the soil reduced the plasticity index by 21% and changed the particle size distribution, reducing the number of clay-sized particles by 72% and increasing the number of sand-sized particles by 158%. The UPV values of the different structures tested showed an increase between 37 and 57.5% up to a curing time of 7 days. The highest value of the collapse potential found were 14.45% for the specimens molded with the lower moisture content with cement addition and inundated at 200 kPa. Stiffer structures may be associated with suction effects in compressibility response, in addition to the increased particle interconnectivity evidenced by ultrasonic testing. Collapse susceptibility was correlated with significant suction effects associated with interconnected porosity. Higher collapse potential values were related to greater stability in unsaturated conditions due to the combined effects of suction and cementitious bonds.
Keywords: Collapse potential; Compressibility; Tropical residual soils; Ultrasonic technique